Postura da mão e imagética motora: um estudo sobre reconhecimento de partes do corpo - LAMEIRA, Allan Pablo do Nascimento (2015)
Objective: Recognition of body parts activates specifi c somatosensory representations in a way that is similar to motor imagery. These representations are implicitly activated to compare the body with the stimulus. In the present study, we investigate the infl uence of proprioceptive information relating to body posture on the recognition of body parts (hands). It proposes that this task could be used for rehabilitation of neurological patients. Methods: Ten right-handed volunteers participated in this experiment. The task was to recognize the handedness of drawings of a hand that were presented in different perspectives and several orientations. For drawings of a right hand, the volunteers pressed the right key, and for drawings of a left hand, they pressed the left key. The volunteers underwent two sessions: one with their hands in a prone posture and the other with their hands in a supine posture. Results: The manual reaction time was longer for perspectives and orientations for which the real movement was diffi cult to achieve. This showed that, during the task, motor representations were activated to compare the body with the stimulus. Furthermore, the subject’s posture had an infl uence in relation to specifi c perspectives and orientations. Conclusions: These results showed that motor representations are activated to compare the body with the stimulus, and that the position of the hand infl uences this resonance between the stimulus and the body part.